2017
DOI: 10.14723/tmrsj.42.57
|View full text |Cite
|
Sign up to set email alerts
|

Orange up-conversion in TiO<sub>2</sub>-ZnO composite ceramics fabricated by metal organic decomposition

Abstract: The phenomenon of photon up-conversion (UC) has attracted considerable research interest for its application to fields as diverse as bioimaging and photovoltaics. In this study, we report on the concentration dependence of Zn 2 TiO 4 :Yb 3+ , Er 3+ on UC emission. Upon investigating Mg, Ti, and Zn as potential UC host materials, we find that the combination of Ti and Zn yields the most increase in luminous efficiency. Further, as a result of varying the molar ratio, a high-intensity emission spectrum is observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…ZnO-TiO 2 oxides are a multifunctional material that have been used in gas sensors [26] and photocatalysts [27,28]. And, we have reported that the PL intensity is increased by mixing TiO 2 and ZnO in comparison to only TiO 2 or only ZnO [29]. However, the luminescence efficiency of a metal oxide is generally lower than that of a halide.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO-TiO 2 oxides are a multifunctional material that have been used in gas sensors [26] and photocatalysts [27,28]. And, we have reported that the PL intensity is increased by mixing TiO 2 and ZnO in comparison to only TiO 2 or only ZnO [29]. However, the luminescence efficiency of a metal oxide is generally lower than that of a halide.…”
Section: Introductionmentioning
confidence: 99%